LIM Proteins in Actin Cytoskeleton Mechanoresponse - Smith, MA (2014)
The actin cytoskeleton assembles into branched networks or bundles to generate mechanical force for critical cellular processes such as establishment of polarity, adhesion, and migration. Stress fibers are contractile, actomyosin structures that physically couple to the extracellular matrix through integrin-based focal adhesions, thereby transmitting force into and across the cell. Recently, LIM domain proteins have been implicated in mediating this cytoskeletal mechanotransduction. Among the more well studied LIM domain adapter proteins is zyxin, a dynamic component of both focal adhesions and stress fibers. Here, we discuss recent research detailing the mechanisms by which stress fibers adjust their structure and composition to balance mechanical forces, and suggest ways zyxin and other LIM domain proteins mediate mechanoresponse.